A New Three-Way Translocation t(4;11;7)(q21;q23;q22) in a Mixed-Phenotype Acute Leukemia. (10th November 2011) - Takasaki, Hirotaka; Tachibana, Takayoshi; Tanaka, Masatsugu; Maruta, Atsuo; Ishigatsubo, Yoshiaki; Kanamori, Heiwa
Abstract : A 68-year-old man was admitted to our hospital in September 2008 because of a left-sided chest pain. Bone marrow examination showed that 85.5% of leukemic cells were positive for myeloperoxidase (MPO) and were negative for esterase stain. Flow cytometric analysis (FCM) revealed the expression of CD19, CD79a, CD13, CD33, CD34, and HLA-DR on the blasts. Cytogenetic analysis of bone marrow cells using the G-banding technique demonstrated 47, XY, +X, t (4;11;7)(q21;q23;q22) in five of the 20 analyzed cells. The patient was diagnosed as having mixed biphenotypic acute leukemia according to the European Group for Immunologic Classification of Leukemia criteria. Mixed-phenotype acute leukemia is a rare, difficult to diagnose entity. Whether patients with mixed-phenotype acute leukemia should be treated with regimens designed for acute myeloid leukemia, acute lymphoblastic leukemia, or both remains unclear.